STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENCEGAH TERJADINYA BULLYING ANTAR SISWA MELALUI PROGRAM PEACEFUL SCHOOL DI SMPN 6 SINGINGI HILIR - Chusnul Chotimah; Bustanur Bustanur; Sopiatun Nahwiyah (Universitas Islam Kuantan Singingi, 2020)
The background of this problem is the rise of negative student behavior, which is a case of unsettling bullying that prevents children from learning at school. Bullying can occur anywhere, including in schools, playgrounds, at home and in entertainment venues. Whereas, if studens are often victims of violence, they can have a bad character in the future. This certainly has a negative impact on the development of the nation. If reviewed in Islamic studies, bullying is the same Al baghyu which is acting arbitrarily, do wrong and persecute others. Therefore the strategis of Islamic religious education teachers in schools is needed to prevent bullying through the peaceful school program.This study aims to describe the forms of bullying among studens who are at SMPN 6 Singingi Hilir, strategies for Islamic religious education teachers to prevent bullying among students through the peaceful school program. This reseach is a qualitative research and data collection techniques used are observation, interviews, and documentation.Data analysis is done to provide, sufficient interpretation of the data collected and compiled to answer the problem statement as a conclusion.The results of the study show, (1) forms of bullying contained in SMPN 6 Singingi Hilir, Physical bullying in the form of taking a tie, hit, pinch, and pick up a pen. Verbal bullying in the form of mocking, dub, cheering, spread false news. Non-verbal bullying in the form of clenching fists. (2) strategies for Islamic religious education teachers to prevent bullying among students through the peaceful school program by mutual trust, cooperation, torerance, acceptance of differences, and respect for environmental sustrainability.